Study on Mechanical Properties of Shale Under Different Loading Rates - Wei, Yuanlong; Zhao, Lingyun; Yuan, Tao; Liu, Wei (Frontiers in Earth Science, 2022)
In the process of shale gas development, different drilling, hydro-fracturing, and pumping speeds will produce different productivity effects. This is a reflection of the loading rate effect on rock mechanics. Therefore, it is of scientific significance to investigate the deformation and damage characteristics of shale under different loading rates. In this paper, a series of indoor experiments were carried out to reveal the loading rate effect of Longmaxi shale, including of SEM, XRD, and uniaxial compression testing under different loading rate. The results show that: 1) The peak strength of shale increases with the increase in loading rate, and does the elastic modulus, but Poisson’s ratio has no obvious regulation with loading rate. In comparison, loading rate induces a variation range of about 20% for the peak strength than elastic modulus. 2) the loading rate has noticeable effects for shale rock failure. Higher rate induces drastic failure but the cracks are simple, lower loading rate leads to complex failure of cracks. The length of failure cracks is largely increased along with decrease of strain rate. So lower strain rate is helpful to form more broken fragment in shale matrix. 3) by analysis the relationship between elastic strain energy/dissipated energy and loading rate, it shows that the elastic strain rate has a preliminary increasing and then decreasing trend with loading rate, but the dissipated energy has a decreasing trend with loading rate. Higher loading rate is helpful for increasing the brittleness of the shale, but lower loading rate is favorable to form more cracks and greater fracturing degree in the shale matrix. Disscussions are made on the effect of loading rate on the mechanical and fracturing properties of the shale. And it is suggested that lower hydro-fracturing rate is useful for generating more complex crack-network in the shale revervoirs.